Portuguese skilled migration in DIOC 2010/11 - Cândido, Ana Filipa (2018)
According to the data of DIOC 2010/11 (Database on Immigrants in OECD Countries), there were one million and 400 thousand Portuguese emigrants in OECD countries. Regarding educational attainment, the majority of Portuguese emigrants had a low level of education, namely in the countries which had the highest stock of migrants. Nevertheless, it is possible to verify a progressive qualification of the emigrants according to the duration of stay. An increase in the number of Portuguese emigrants which have a high level of education has been recorded when the duration of stay is more recent, i.e., one year or less. Thereby, the recent emigration tends to be a more skilled one.